Soil Management in the Breede River Valley Wine Grape Region, South Africa. 1. Cover Crop Performance and Weed Control - Fourie, J.C. (South African Journal of Enology and Viticulture, 2016)
Eight cover crop treatments were applied for 12 consecutive years on a medium-textured soil in a vineyard near Robertson (33Ëš50’S, 19Ëš54’E). A treatment with full surface straw mulch and full surface post-emergence chemical control applied from just before grapevine bud break to harvest (BB), and one with no cover crop combined with BB, were also applied. The control consisted of mechanical control in the work row and post-emergence chemical control in the vine row applied from bud break to harvest. Rotating Triticale v. Usgen 18 (triticale) and Vicia dasycarpa Ten. (vetch) did not improve the dry matter production (DMP) of either species. Average DMP decreased as follows: triticale > Secale cereale L. v. Henog (rye)/Vicia faba L. v. Fiord (faba bean) mixture > triticale/vetch biennial rotation > triticale/vetch annual rotation > vetch. Triticale (BB) resulted in total winter weed suppression from 1995 to 1996 and from 2001 to 2004. Total weed control from bud break to the pea size berry stage of the grapevines was achieved with straw mulch (BB), triticale (BB), rye/faba bean mixture (BB) and triticale/vetch rotated biennially (BB) from 2001 to 2003. For triticale combined with full surface post-emergence chemical control applied from grapevine berry set (AB), and for triticale/vetch rotated annually (BB), this was restricted to 2001 and 2003. From the pea size berry stage to harvest, straw mulch (BB), triticale (BB), vetch (BB), rye/faba bean mixture (BB) and triticale (AB) reduced the weed stand significantly in comparison to the control.